ANTIMICROBIAL SUSCEPTIBILITY OF VIRIDANS GROUP STREPTOCOCCI ISOLATED FROM BLOOD OF HOSPITALIZED PATIENTS - RICHA ROY, (The Bioscan, 2012)
The present paper describes the results of blood samples were collected and cultured from 100 patients hospitalized during the period of March 2009 to May 2009, in the regional hospitals at Allahabad (UP). Fifty nine blood culture samples were positive for Streptococcus sp., of which 21 VGS strains were isolated. The isolates were identified on the basis of cultural, morphological characteristics and biochemical tests were performed for antibiotic susceptibility. The 21 VGS strains isolated from the blood culture included, S. mitis (37%), S. intermedius (23.08%), S. sanguis (21%), S. salivarius (14.28%) and S. mutans (11%). Among the different risk factors evaluated viz. age and sex, socio-economic status, duration of hospitalization and fever, sex of patients showed a significant association (p<0.05) with the incidence of VGS strains causing infection in the blood of hospitalized patients. The antibiotic sensitivity test was done by disc diffusion method. All VGS strains isolated showed resistance towards Penicillin and Vancomycin but were sensitive towards Erythromycin, Meropenem, Tetracycline, Azithromycin, Gatifloxacin and Ciprofloxacin. S. mitis and S. sanguis demonstrated resistance towards Ampicillin, however, S. mutans, S. salivarius and S. intermedius showed intermediate sensitivity to Ampicillin. There has been a drift in susceptibility patterns, with resistance issues seen in the general population of hospitalized patients now emerging in febrile neutropenic patients.